2013
DOI: 10.1016/j.exphem.2013.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Increased uptake by splenic red pulp macrophages contributes to rapid platelet turnover in WASP(–) mice

Abstract: Thrombocytopenia due to rapid platelet consumption contributes to the severe thrombocytopenia of the Wiskott Aldrich Syndrome (WAS), and to the milder thrombocytopenia seen in murine WAS. Here we show that rapid clearance of 111In labeled murine WASP(−) platelets correlates with enhanced splenic uptake. Using platelets labeled with a pH sensitive fluorescent marker (pHrodo), we quantify normal platelet uptake by red pulp macrophages (RPM), and demonstrate its enhancement after in vivo opsonization of platelets… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 22 publications
1
8
0
Order By: Relevance
“…Consistently, PLTs that are isolated from patients with WAS have increased PS exposure, Ca 2+ flux, and microparticle release that contribute to their peripheral elimination as demonstrated by the colocalization of PLTs and macrophages found in the splenic histologic sections of splenectomized patients with WAS . Murine studies have confirmed the increased consumption of Was −/− PLTs and in vitro opsonization by BM‐derived macrophages or in vivo opsonization by splenic red pulp macrophages . In line these results, labeled PLTs that were isolated from patients with WAS or XLT were more susceptible to ex vivo phagocytosis by activated THP‐1 cells; however, the analysis of PS exposure resulted in contrasting data that indicate enhanced or normal expression both in patients and in the two different murine models .…”
Section: Wasp and Pltssupporting
confidence: 62%
See 1 more Smart Citation
“…Consistently, PLTs that are isolated from patients with WAS have increased PS exposure, Ca 2+ flux, and microparticle release that contribute to their peripheral elimination as demonstrated by the colocalization of PLTs and macrophages found in the splenic histologic sections of splenectomized patients with WAS . Murine studies have confirmed the increased consumption of Was −/− PLTs and in vitro opsonization by BM‐derived macrophages or in vivo opsonization by splenic red pulp macrophages . In line these results, labeled PLTs that were isolated from patients with WAS or XLT were more susceptible to ex vivo phagocytosis by activated THP‐1 cells; however, the analysis of PS exposure resulted in contrasting data that indicate enhanced or normal expression both in patients and in the two different murine models .…”
Section: Wasp and Pltssupporting
confidence: 62%
“…98 Murine studies have confirmed the increased consumption of Was −/− PLTs and in vitro opsonization by BM-derived macrophages 108 or in vivo opsonization by splenic red pulp macrophages. 110 In line these results, labeled PLTs that were isolated from patients with WAS or XLT were more susceptible to ex vivo phagocytosis by activated THP-1 cells; 111 however, the analysis of PS exposure resulted in contrasting data that indicate enhanced or normal expression both in patients and in the two different murine models. 93,96,104,107,[109][110][111][112][113] In addition, splenectomy, despite inducing an increase in PLT count and size, does not normalize the counts, which suggests that phagocyte-mediated PLT elimination is not the only mechanism responsible for thrombocytopenia.…”
Section: Pathogenesis Of Thrombocytopenia In Wasmentioning
confidence: 90%
“…The spleen is a major site of platelet sequestration, and splenic phagocytes can remove activated or senesced platelets. 49,50 Therefore, we examined the spleen for evidence of enhanced uptake of labeled platelets within splenic macrophages (CD11b 1 F4/80 1 ) by flow cytometry (gating strategy in supplemental Figure 2B). In DENV-infected mice, total numbers of free-labeled platelets in the spleen were reduced compared with uninfected controls ( Figure 1G), suggesting against sequestration.…”
Section: Denv-induced Thrombocytopenia Is Caused By Platelet Destructmentioning
confidence: 99%
“…Studies carried out in these mutants demonstrated defective and premature thrombopoiesis 18 and increased peripheral elimination of Was −/− platelets mediated by macrophages and anti-platelet autoantibodies (anti-PLT autoAbs). 1921 However, because all previous studies were performed in murine mutants or in patients lacking WASp in all hematopoietic lineages, it remains difficult to discriminate the contribution of the defective immune system to platelet defect. To this end, we generated a conditional Was −/− mouse model (CoWas) lacking WASp only in the megakaryocytic lineage.…”
mentioning
confidence: 99%